2014
DOI: 10.5713/ajas.14.0328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Coconut Oil as a Medium-chain Fatty Acid Source on Performance, Carcass Composition and Serum Lipids in Male Broilers

Abstract: This study was conducted to investigate the effects of dietary coconut oil as a medium-chain fatty acid (MCFA) source on performance, carcass composition and serum lipids in male broilers. A total of 540, one-day-old, male Arbor Acres broilers were randomly allotted to 1 of 5 treatments with each treatment being applied to 6 replicates of 18 chicks. The basal diet (i.e., R0) was based on corn and soybean meal and was supplemented with 1.5% soybean oil during the starter phase (d 0 to 21) and 3.0% soybean oil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 35 publications
6
50
1
4
Order By: Relevance
“…They are, therefore, promising candidates for obesity therapeutics . Previous studies using dietary coconut oil have shown its health benefits toward hepatotoxicity, together with altered lipid profiles in the body . Another unique feature of coconut oil is the low abundance of both n‐3 and n‐6 essential FAs.…”
Section: Introductionmentioning
confidence: 99%
“…They are, therefore, promising candidates for obesity therapeutics . Previous studies using dietary coconut oil have shown its health benefits toward hepatotoxicity, together with altered lipid profiles in the body . Another unique feature of coconut oil is the low abundance of both n‐3 and n‐6 essential FAs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, according to Miller et al () demonstrated that the result of ADG was influenced by the level of somatotropin in MCFAs diet supplementation. However, Wang et al () indicated that supplementation of dietary coconut oil which is a source of MCFAs did not have any significant effect on weight gain and feed intake in broilers. The ADFI and G/F of pigs were not affected by dietary MCFAs supplementation in this experiment which agrees with the studies of Hong et al, () and Hanczakowska et al, ().…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that the replacement of soyabean oil by coconut oil in the feed of broilers lowered the level of low density lipoprotein (LDL)-cholesterol and favourably affected lipid profile in serum (Wang et al, 2015). It is plausible that this effect may be related to the altered expression of miR-122a.…”
Section: Discussionmentioning
confidence: 99%